Processing and formulation insights for designing quality into lyophilised biopharmaceuticals - Beech, Karen E. (2015)
This thesis makes an original contribution to the field of formulation development by providing new experimental data and insights into the effect of processing and formulation conditions on the quality of lyophilised biopharmaceuticals. The quality attributes of lyophilised products include: a quick reconstitution time, product elegance and protein stability, which are known to be affected by processing and formulation parameters. However, choice of formulation excipients or processing conditions often relies on previous experience rather than mechanistic insight. The motivation of this thesis was therefore to provide a greater understanding of how process variables andexcipient choice affect these quality attributes. Bovine serum albumin (BSA) and immunoglobulin G (IgG) were used as model proteins to investigate formulation conditions, which included the excipient, the lyophilisation cooling profile and duration of the annealing step. BSA was also used as a model protein to explore the effects of sucrose and arginine as lyoprotectants. Unique to this study was the investigation of arginine salts as lyoprotectants, wherein the counterions were dicarboxylic acids with increasing chain length. Two key results regarding quality attributes were observed. Firstly, characterisation of the lyophilised structure established that there was an optimal annealing time, beyond which there was an increase in primary drying time, batch heterogeneity and variable moisture content. Secondly, a relationship was found between decreasing dicarboxylic acid chain length and improved protein stability. To explain these findings, two mechanisms are proposed that account for ice crystal growth during annealing and the observed changes in protein stability at the molecular level. Significantly, this research provides insights for future formulation development studies.